PENINGKATAN KETERAMPILAN MENULIS KARANGAN NARASI SISWA KELAS III SDN 004 BATURIJAL HULU KECAMATAN PERANAP DENGAN MENERAPKAN MODEL PEMBELAJARAN THINK TALK WRITE - Aida Nursanti (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2020)
The problem in this research is the low skill of writing narrative essays for third grade students of SDN 004 Baturijal Hulu, from 27 students, 2 students with very skilled category; students with the skilled category 5 students; 10 students categorized as skilled enough; 10 students in the less skilled category. The method used in this research is classroom action research, which is conducted in 2 cycles which aims to improve the writing skills of third grade students of SDN 004 Baturijal Hulu by applying the Think Talk Write (TTW) learning model. The subjects of this study were third grade students of SDN 004 Baturijal Hulu. Data obtained through observation and tests. Meanwhile, the results of narrative essay writing skills after applying the Think Talk write learning model increased at UH1 with an average of 74.70 with a large increase from the basic score of 14.52% and the average UH II was 84.70 with a large increase in score. the base of 24.52%. Based on the results of this study, it can be concluded that the implementation of the Think Talk Write (TTW) learning model can improve the narrative writing skills of grade III students of SDN 004 Baturijal Hulu.